Image recorder server with IP camera and pocket PC - Boonma, N.; Sangthong, A.; Mitatha, S.; Vongchumyen, C. (My University, 2011)
We propose a new system for image recorder server from IP camera. The system consists of 2 parts, Server and viewer. Server is software running on PC with ability to capture image from IP camera and save to disk like an image server. The second part is the viewer. A user be able to monitor and view the saved image on the server via a web-based application from everywhere with password protection. Live and history image can be show to user to check the status of area or investigate the history event. Further more. The server can connect to IP camera to collect image or connect a web cam directly to the server for cost reduction. Finally, the user can view the image by using browser on the PC or Windows mobile phone.
Keywords: Image recorder; IP Camera; Pocket PC; web-based application; Windows mobile